Simplified equivalent multiple baseline solutions with elevation-dependent weights - Shen, Y.; Li, Bofeng; Xu, G. (Springer, 2009)
Since the assumption of all stations tracking the same satellites with identical weights was previouslyemployed by Shen and Xu (GPS Solut 12:99?108, 2008) to derive the simplified GNSS single- and double-differenced equivalent equations, this supplementary paper expands these simplified equations in the case of each station tracking different satellites with elevation-dependent weights. Numerical experiments are performed to demonstrate the computational efficiency of the simplifiedequivalent algorithm relative to the traditional method in various scenarios of multi-baseline solutions with tracking different satellites. The fast computational speed of the simplified equivalent algorithm will potentially benefit the local, regional and even global GNSS multi-baseline solutions as well as the combined GNSS application.